1994
DOI: 10.2105/ajph.84.8.1255
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and mortality in older community residents.

Abstract: OBJECTIVE. Cognitive impairment among the elderly has been linked to mortality in studies of clinical populations. The purpose of this study was to examine the mortality risk associated with cognitive impairment among elderly populations in the community. METHODS. Cognitive impairment and other social and health factors were assessed in 1855 elderly community residents. This sample was reinterviewed periodically to assess changes in health and survival. RESULTS. At baseline 33% of the sample were mildly impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
107
7
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 46 publications
10
107
7
4
Order By: Relevance
“…Some studies have reported weak abilities to predict mortality (45), whereas others have described memory as a strong predictor (3,9). Contrary to our findings, several studies have reported the MMSE to be a good predictor of mortality (11,17,46). These studies did not include such a broad range of health measures as our study did, which may explain the discrepancy in results.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Some studies have reported weak abilities to predict mortality (45), whereas others have described memory as a strong predictor (3,9). Contrary to our findings, several studies have reported the MMSE to be a good predictor of mortality (11,17,46). These studies did not include such a broad range of health measures as our study did, which may explain the discrepancy in results.…”
Section: Discussioncontrasting
confidence: 99%
“…Health measures were selected because they encompass a broad range of health aspects. Moreover, the questions on self-rated health (29), functional limitations (11,17), medication use (29), and the presence of chronic diseases (30) as well as tests of lung function (31) and physical performance (32) have been shown to be associated with mortality in older adults.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet there are several other studies based on non-populational samples 13,14,16,18,29,32 , or based on populational samples that were not originally designed to assess only elderly people 3,15,20,30 .…”
Section: Introductionmentioning
confidence: 99%
“…Desde hace unos años se están creando registros de demencias que en un futuro suministraran información muy valiosa sobre estas enfermedades en España 7,8 . Pero desde la perspectiva poblacional existen pocos indicadores para conocer la prevalencia y tendencia de este importante problema de salud pública y aunque la mortalidad no es un buen indicador para conocer qué ocurre en la población con las enfermedades crónicas degenerativas que son altamente prevalentes pero producen pocas defunciones, en el caso de las demencias, por su origen orgánico y el deterioro físico que producen, pueden ser consideradas causas importantes de defunción 9 . Las demencias irreversibles en las que se incluye la enfermedad de Alzheimer, fueron la octava causa de mortalidad en 2003 y la séptima en los años del 2004 al 2006 en los Estados Unidos 10,11 .…”
Section: Introductionunclassified